S15.3 European MSM Internet Survey (EMIS): differences in sexually transmissible infection testing in European countries. (10th July 2011) - Marcus, U; Schmidt, A J; Breveglieri, M; Davila, P F; Ferrer, L; Folch, C; Hickson, F; Hospers, H J; Mirandola, M; Reid, D; Weatherburn, P; ,
Abstract : Background: Comparing rates of sexually transmissible infections (STIs) among men who have sex with men (MSM) in different European countries is challenging due to national differences in reporting systems, healthcare systems, infectious disease surveillance methods, quality of data, and/or levels of social acceptance of homosexual behaviours and openness about homosexuality. Methods: From June through August 2010, the European MSM Internet Survey (EMIS) mobilised more than 180 000 respondents from 38 European countries to complete an online questionnaire in one of 25 languages. The questionnaire covered sexual happiness, HIV and STI-testing and diagnoses, unmet prevention needs, intervention performance, HIV-related stigma and gay-related discrimination. Recruitment was organised predominantly online, through gay social media, and links and banners on more than 100 websites for MSM all over Europe. Results: Perceptions on access to free/affordable STI-testing differed across Europe (median: 80%; range: 40–95%); and was substantially correlated with reported recent STI-testing (R 2 =0.27). Quality of STI-testing was highly diverse: While blood-testing was common in all participating countries, only Ireland, Malta, and the UK seem to offer penile or particularly anal examinations as standard of care. In all participating countries HIV-positive respondents reported higher rates of both STI-testing and diagnosis. Self-reported STI-screening among men without HIV diagnosis ranged from 10% (Turkey) to 37% (Netherlands). Substantial correlations between rates of testing procedures appropriate for MSM (such as anal or genital swabs) and diagnosed gonorrhoea (R 2 HIV-pos=0.24) or Chlamydia infections were observed (R 2 HIV-pos=0.50; R 2 others=0.29). Conclusion: Self-reported testing and diagnosis rates for bacterial STIs suggest high levels of under-diagnosis and unmet sexual healthcare needs in most European countries. In Europe, there is an urgent need to implement or improve sexual healthcare tailored to MSM-specific needs.